BS49 Human embryonic stem cell derived cardiomyocytes express functional receptors for the cardiovascular peptide apelin. (May 2019) - Macrae, Robyn; Bernard, William G.; Kuc, Rhoda E.; Colzani, Maria T.; Williams, Thomas; Nyimanu, Duuamene; Maguire, Janet; Sinha, Sanjay; Davenport, Anthony P.
Abstract : Introduction: The apelin receptor is expressed throughout the cardiovascular system, including in cardiomyocytes. Receptor activation by either of its endogenous peptide ligands, apelin or Elabela, has a positive inotropic effect and promotes vasodilatation. Human embryonic stem cell (hESC)-derived cells have the potential for use in translational research to investigate cellular signalling, disease pathogenesis and potential novel treatments. Our aim was to determine if hESC-derived cardiomyocytes express apelin receptor protein and to quantify receptor density to ascertain if this cell type can be used as a phenotypic model for human diseases associated with apelin receptor mutations. Methods: H9 hESCs were cultured to induce differentiation to beating cardiomyocytes. Saturation radioligand binding experiments were performed using [Glp65, Nle75, Tyr77][125I]apelin-13 and [Pyr1]apelin-13 to define non-specific binding. Bound radioactivity was counted and data analysed using iterative curve fitting programs to obtain values of receptor affinity (KD) and density (BMAX). Immunocytochemistry was carried out using anti-apelin receptor or anti-cardiac cell marker antibodies. Results: Previous work demonstrated expression of the apelin receptor in hESC-derived cardiomyocytes at the gene level by qRT-PCR at similar levels to adult cells (figure 1A). Here, radioligand binding studies have confirmed receptor protein expression in beating hESC-derived cardiomyocytes. Binding was saturable and [125I]apelin-13 bound with sub-nanomolar affinity (0.12 nM) and receptor density found to be 21 fmol/mg (figure 1B), comparable to that found in human adult heart. Hill slope was close to 1 consistent with a single binding site for apelin in these cells. Furthermore, beating hESC-derived cardiomyocytes stained positive for apelin receptor, in addition to the standard cardiac markers including cardiac troponin T (figure 2 ). Conclusion: These data importantly confirm that hESC-derived cardiomyocytes express apelin receptor protein at similar levels to adult human heart. Apelin receptor mutations have been identified in the 100, 000 Genomes Bridge Project that are associated with rare diseases, including pulmonary arterial hypertension. Our ongoing experiments aim to pharmacologically characterise the apelinergic signalling pathway in the beating hESC-derived cardiomyocytes and we propose to generate hESC-derived phenotypic models by introducing selected apelin receptor mutations via CRISPR/Cas-9 gene editing. Conflict of interest: None